The Effect of the Comprehensive Midwifery Care Model with the One Student One Client (OSOC) Approach to Birth Outcomes in North Aceh Regency - Rildayani Rildayani; Nurjannah Nurjannah; Irwan Saputra; Cut Meurah Yeni; Said Usman (Budapest International Research and Critics University, 2020)
Maternal and Newborn Health is a priority as the main indicator in health. During the pregnancy period until the puerperium it is estimated that as many as 15% can experience life-threatening complications of the mother and baby. However, this death is considered to be prevented through the provision of comprehensive care that can be done with the One Student One Client (OSOC) approach, which is an activity that exists between low-risk pregnant women and midwife students during pregnancy up to 6 weeks post delivery. Objective: This study aims to assess the relationship of comprehensive midwifery care with the One Student One Client (OSOC) approach to birth outcomes (gestational age at delivery, prolonged labor and asphyxia) Method: This study is a retrospective cohort study, using secondary data from medical record documentation Results: Comprehensive midwifery care with the OSOC approach was associated with the occurrence of prolonged labor p value 0.046 (RR 95% CI; 3.2 (1.08-9.74), asphyxia with p value 0.037 (RR 95% CI; 2.57 1.12-6.50) Conclusion: The OSOC method can be used in comprehensive midwifery care for all mothers and babies from pregnancy up to 6 weeks post delivery in an effort to improve birth outcomes.